Technology and Social Bonds: Exploring the Dynamics of Human Connection in the Society 5.0 Era - Faresta, Rangga Alif; Nicholas, Teo Zhao Ser Bryan; Chi, Yixuan (International Journal of Ethnoscience and Technology in Education, 2025)
In the Society 5.0 era, human connections are profoundly influenced by technological advancements, particularly social media. This study explores the impact of these changes on social bonds, emphasizing the balance between connectivity and relationship quality. Using a descriptive survey method, data were gathered from 147 participants through a structured questionnaire. The findings reveal that while digital platforms enhance communication frequency, facilitate long-distance relationships, and broaden cultural understanding, they also present challenges such as reduced face-to-face interactions, dependency on digital tools, and superficial connections. Participants widely recognized the role of technology in creating opportunities for new relationships and sustaining existing ones across distances. However, they also emphasized the enduring value of physical interactions for emotional depth and trust. Moderate levels of agreement regarding digital distractions and technology’s role in conflict resolution reflect the complexities of navigating these tools in everyday relationships. The dual nature of technologyâ€”as both a connector and a potential disruptorâ€”highlights the need for strategies to promote mindful and balanced usage. This study underscores the importance of fostering digital literacy and encouraging offline engagement to preserve meaningful social bonds. By addressing these dynamics, Society 5.0 can strengthen inclusivity, empathy, and cohesion, ensuring that technological progress aligns with human well-being and authentic connections.